Development of nanocrystalline ironchromium alloy by means of sintering and ion implantation for interconnect application in high-temperature solid oxide fuel cells - Khaerudini, Deni Shidqi (2011)
This research is aimed to develop the nanocrystalline iron-chromium (FeCr) alloys by two different sintering methods, spark plasma sintering (SPS) and hot pressing (HP). The sintering temperatures in SPS are designed at 800 and 900 o C; meanwhile o in HP at 1000 C. The lower sintering temperature in SPS than HP was carried out in order to obtain the relatively similar in theoretical density of alloy with a minimum grain growth. The alloy has a potential application as interconnector in solid oxide fuel cell (SOFC). The beneficial effect of the reactive element by means of lanthanum (La) into the alloys surface which is introduced using ion implantation is also evaluated. The study focused on the properties, including thermal expansion, oxidation behaviour and electrical resistance of the surface oxide scales. Oxidation testing was conducted at 900-1100 o C for 100 h in laboratory air. Characterizations by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were carried out before and after each route or process to investigate the microstructure, phase change, and formation of the oxide layer. The specific aspects studied were the effects of nanocrystalline structures, which influenced by the sintering method; and surface treatment through La ion implantation of chromia-forming alloys may improve their high thermal stability. The commercially available ferritic steel is chosen as the comparison with other high-Cr ferritic model alloys. The results revealed that the FeCr alloy prepared by SPS, to be more effective to retain nanocrystalline and better properties than those prepared by HP and commercially available ferritic steel. For all types of materials, the presence of La had no detectable effect on thermal expansion but a major effect on oxide scale adherence. The results consistently showed that better reduction in electrical resistance corresponds with excellent oxidation resistance of the alloy. The performance of FeCr alloy sintered by SPS and implanted by La exhibited the lowest oxidation and electrical resistance of the oxide scale.